Valuable lessons from two different situations: C.O.D.E.S.A. versus Oslo, could techniques from South Africa assist conflict resolution in Israel/Palestine - Katzenstein, Michael (My University, 2010)
The processes of both C.O.D.E.S.A. and Oslo took place under extremely testing environments, and whilst the situation in Israel/Palestine and that of South Africa during the apartheid years were completely different the negotiation and diplomatic processes that took place in the respective regions may have valuable lessons to teach the other. While C.O.D.E.S.A. was a success and The Oslo Accords did fail. The South African context and the negotiations that succeeded may have precious insight for future conflict resolution in the region of Israel/Palestine.